The unique biology of catch muscles: insights into structure, function, and robotics innovations - Vyatchin, Ilya; Dyachuk, Vyacheslav (Frontiers in Bioengineering and Biotechnology, 2025)
The Review covers the current state of functions, neurotransmitter innervation, the structure, and development of the contractile apparatus of unique group of catch muscles inherent only to bivalves. In contrast to conventional muscles, during contraction and relaxation, catch muscles possess a unique ability to enter the contraction holding state, referred to as catch state. The latter consists in energy-efficient maintenance of long-lasting tension developed by the muscle without consuming ATP-derived energy and regulated by serotonin and acetylcholine. Despite the molecular mechanism of catch state phenomenon still remains unclear, the combination of experimental data and the resulting assumptions allow one to design new energy-efficient and chemically-driven artificial muscles. The analysis of the structure and function of the catch muscles in this work opens the way to a conceptually new strategy for energy-efficient biomimetic robotics, including underwater robotics.